2016
DOI: 10.1128/aac.00834-16
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing the Nonsteroidal Anti-inflammatory Drug Diflunisal as an Osteoprotective, Antivirulence Therapy for Staphylococcus aureus Osteomyelitis

Abstract: dStaphylococcus aureus osteomyelitis is a common and debilitating invasive infection of bone. Treatment of osteomyelitis is confounded by widespread antimicrobial resistance and the propensity of bacteria to trigger pathological changes in bone remodeling that limit antimicrobial penetration to the infectious focus. Adjunctive therapies that limit pathogen-induced bone destruction could therefore limit morbidity and enhance traditional antimicrobial therapies. In this study, we evaluate the efficacy of the U.S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 27 publications
5
51
0
1
Order By: Relevance
“…82 Some identified quorum sensing inhibitors include savirin, 83 Hamamelitannin, 82,84 farnesol, [85][86][87] and the nonsteroidal anti-inflammatory drug (NSAID) diflunisal. 88 In one study, the antimicrobials cefazolin, cefalonium, cephalexin, cefoxitin, daptomycin, linezolid, tobramycin, and fusidic acid were tested alone or with Hamamelitannin against in vitro S. aureus biofilms. In all cases except fusidic acid, treatment with the quorum sensing inhibitor was superior to antimicrobial monotherapy.…”
Section: Quorum Sensing Inhibitorsmentioning
confidence: 99%
“…82 Some identified quorum sensing inhibitors include savirin, 83 Hamamelitannin, 82,84 farnesol, [85][86][87] and the nonsteroidal anti-inflammatory drug (NSAID) diflunisal. 88 In one study, the antimicrobials cefazolin, cefalonium, cephalexin, cefoxitin, daptomycin, linezolid, tobramycin, and fusidic acid were tested alone or with Hamamelitannin against in vitro S. aureus biofilms. In all cases except fusidic acid, treatment with the quorum sensing inhibitor was superior to antimicrobial monotherapy.…”
Section: Quorum Sensing Inhibitorsmentioning
confidence: 99%
“…Treatment with naringenin, a flavonoid present in grapefruits and tomatoes, reduced transcription of S. aureus genes encoding AgrA and alpha-toxin, attenuating alpha-toxin mediated injury to alveolar epithelial cells, and reduced pulmonary inflammation and injury in a mouse pneumonia model [44]. Very recently, the nonsteroidal anti-inflammatory drug diflunisal was shown to block S. aureus AgrA transcriptional regulation of small peptide toxin virulence factors known as phenol soluble modulins (PSMs); diflunisal treatment reduced PSM production and diminished bone destruction in a murine osteomyelitis model of infection [45]. …”
Section: Neutralization Of Virulence Factors: Disarming the Pathogenmentioning
confidence: 99%
“…A recent study found that the FDA-approved nonsteroidal anti-inflammatory drug diflunisal inhibits the agr quorum-sensing system and downstream toxin production through inhibition of AgrA’s binding to the promoter P3 (possibly interrupting the phosphorylation of AgrC) to induce the transcription of various virulence factors [66]. Local delivery of diflunisal during experimental osteomyelitis was highly efficacious in limiting bone destruction in an experimental model of osteomyelitis, despite having no significant effect on bacterial burdens at the site of infection [69]. In vitro , diflunisal decreased the production of osteolytic toxins known as phenol-soluble modulins, providing a mechanistic basis for the decrease in cortical bone destruction in vivo [69].…”
Section: 0 Bodymentioning
confidence: 99%
“…Local delivery of diflunisal during experimental osteomyelitis was highly efficacious in limiting bone destruction in an experimental model of osteomyelitis, despite having no significant effect on bacterial burdens at the site of infection [69]. In vitro , diflunisal decreased the production of osteolytic toxins known as phenol-soluble modulins, providing a mechanistic basis for the decrease in cortical bone destruction in vivo [69]. Future studies will determine whether such an approach improves traditional antimicrobial therapy by limiting bone destruction and potentially improving antimicrobial penetration into infected tissues.…”
Section: 0 Bodymentioning
confidence: 99%